Feasibility of large-scale cholesterol screening: experience with a portable capillary-blood testing device. - Greenland, P (1987)
We conducted a voluntary cholesterol screening in a medical/occupational setting using the Eastman Kodak Ektachem (desk top) blood analyzer. In 10 hours, five technicians performed a finger-stick puncture on 1,081 screenees, 17.7 per cent of whom were classified as moderate-to-high risk. The cost per screenee was under $3; cost per moderate-to-high risk case was under $16. Turn-around time from check-in to report of result was under one hour. This project suggests the feasibility and acceptability of large-scale cholesterol blood screening.